LC/MS/MS structure elucidation of reaction intermediates formed during the TiO2 photocatalysis of microcystin-lr - Shoemaker, Jody A.; De La Cruz, Armah A.; Antoniou, Maria G. (My University, 2008)
Microcystin-LR (MC-LR), a cyanotoxin and emerging drinking water contaminant, was treated with TiO2 photocatalysts immobilized on stainless steel plates as an alternative to nanoparticles in slurry. The reaction intermediates of MC-LR were identified with mass spectrometry (MS) at pH of Milli-Q water (pHsq=5.7). Eleven new [M+H]+ were observed in the liquid chromatography mass spectrometry (LC/MS) chromatogram with some of them giving multiple peaks. Most of these reaction intermediates have not been reported from previous studies employing TiO2 nanoparticles at acidic conditions (pH=4.0). Investigating the effects of pH (for 3.0<pH<7.0), toxin adsorption and initial toxin concentration on the degradation efficiency of the TiO2 photocatalytic films showed that acidic conditions are preferable for the degradation. Combined with the limited surface area of the films and the absence of additional oxidants (i.e., H2O2) the degradation was slower and more intermediate steps were identified. Possible structures of the intermediates (formed at neutral pH) after analyzing the corresponding MS/MS spectra are reported. The collision-induced dissociation of the [M+H]+ of MC-LR and the intermediates 1011.5 and 1029.5 are discussed and possible fragmentation pathways and mechanisms are also proposed. Analysis of the MS/MS spectra indicates that the fragmentation of some amino acids is less favorable because of internal interaction with free groups of adjacent amino acids. The MS/MS spectra assisted in determining hydroxylation sites, by the formation or alteration of specific product ions such as m/z 599.
Keywords: Cyanobacterial toxins; Mass spectrometry; Chemical structure; Liquid chromatography